Influence of structural disorder on the photocatalytic properties of ZnS nanocrystals prepared by the one-pot solvothermal approach - Benatto, Victoria Gabriela; Da Silva Lopes Fabris, Guilherme [UNESP]; Sambrano, Julio Ricardo [UNESP]; Taft, Carlton Anthony; De Almeida La Porta, Felipe (Ecletica Quimica, 2022)
This study focuses on the impact of the sulfur vacancies on the photocatalytic response of the ZnS nanocrystals synthesized by solvothermal method varying the concentration of zinc acetate/thiourea precursors. XRD patterns show that these samples have a hexagonal structure with different degrees of crystallinity, varying the crystallite size from 2.48 to 2.85 nm. The UV-Vis data reveals an absorption peak (at about 320 nm) characteristic of ZnS nanocrystals. As a result, a decrease in the bandgap value of these materials was observed from 3.78 to 3.62 eV. In principle, a comparison of these results and theoretical calculations reveals the formation of intermediate levels inside the bandgap due to structural polarization. These findings also corroborate the zeta potential measured for these samples, evidenced by an increase of positive charge of ZnS surfaces. Also, the low Miller-index surfaces, such as (101-0), (112-0) and (0001), were investigated by periodic density functional theory calculations, in nice agreement with the experimental data. A photocatalysis mechanism was investigated and confirmed the formation of reactive oxygen species.
Keywords: density functional theory; electronic structure; photocatalysis properties; solvothermal processing; ZnS